Do not trash the incentive! Monetary incentives and waste sorting - Alessandro Bucciol; Natalia Montinari; Marco Piovesan (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
This paper examines whether monetary incentives are an effective tool for increasing domestic waste sorting. We exploit the exogenous variation in the waste management policies experienced during the years 1999-2008 by the 95 municipalities in the district of Treviso (Italy). We estimate with a panel analysis that pay-as-you-throw (PAYT) incentive schemes increase by 12.3% the sorted-total waste ratio. This increase reflects a change in the behavior of households, who keep unaltered the production of total waste but sort it to a larger extent. Our data show that household behavior is also influenced by the policies of adjacent municipalities.
Keywords: D01; D78; Q53; 330; incentives; environment; waste management; PAYT; Abfallvermeidung; Abfallabgabe; Italien